Dental Health Assessment in Pediatric Patients with 22q11.2 Deletion Syndrome - Marta Łyszczarz; Agnieszka Moll-Maryńczak; Sylwia Majewska-Beśka; Krzysztof Zeman; Marcin Tkaczyk (European Journal of Dentistry, 2026)
Abstract The aims of this study were to provide a comprehensive evaluation of the dental status in pediatric patients with 22q11.2 deletion syndrome (22q11.2DS) and to analyze the associations between clinical dental findings, general medical conditions, and oral hygiene habits. The cross-sectional study included 20 children (10 girls, mean age 6.45 years) with a confirmed diagnosis of 22q11.2DS. Each child underwent a detailed dental examination, including caries (dmft/DMFT: decayed, missing, and filled teeth index for primary and permanent teeth), developmental defects of enamel (DDE), hypodontia, occlusal relationship disorder, and soft tissue findings assessment. Additionally, the functioning of the oral cavity, especially speech and swallowing patterns, was evaluated. Dental findings were correlated with medical history, oral hygiene habits, and laboratory results, with a specific focus on calcium-phosphate metabolism and immunological parameters. Categorical variables were reported as counts and percentages, while continuous variables were presented as medians and interquartile ranges. Nonparametric methods, including Fisher's exact test and the Mann–Whitney U test, were used for group comparisons. Correlations were assessed using Pearson's (r) and Spearman's rank correlation coefficients. All tests were two-tailed with a significance level of α = 0.05. DDE were identified in 13 (65%) children, of whom 6 (30%) were presented with only hypomineralization, 4 (20%) exhibited only hypoplasia, and 3 (15%) demonstrated both defects. Caries prevalence was 70%, with a mean dmft of 4.65 (standard deviation [SD] 5.05) and DMFT of 8.6 (SD 5.77). Occlusal relationship disorders were observed in 11 (55%) children and hypodontia in 3 (15%) children. Age was the most significant variable associated with caries experience (r = 0.73, p < 0.001), while dysmorphic features were the only significant factor for DDE (p = 0.022). No significant correlations were found between dental findings and laboratory parameters or oral hygiene habits. The most common dental manifestations of 22q11.2DS are DDE, dental caries, and oral dysfunctions. No direct correlation was found between oral health and immunological status or calcium-phosphorus metabolism. Caries is a significant problem and more dependent on age than on oral hygiene alone. Patients require early, comprehensive, and coordinated care from dentists, orthodontists, and speech-language pathologists.